Primer registro de nidificación en ambiente fluvial (Río Negro, Argentina) del Gaviotín Sudamericano Sterna hirundinacea - Petracci, Pablo F. (1997)
We describe a breeding co1ony of South American Tern Sterna hirundinacea in an island of the Río Negro river, 45 km NW of the city of Viedma, Argentina. It is the first record of a breeding colony of this species in a riverine environment.